(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
The rapid proliferation of blockchain technology has not only transformed financial systems but has also fostered the emergence of distinct online communities. Research has primarily focused on the technical, ethical, and financial aspects of blockchain technology, with limited attention given to its linguistic dimension. These communities exhibit unique linguistic practices that both shape and reflect their members’ identities. Therefore, this study is aimed at investigating the interplay between language and identity within select blockchain communities, to understand how linguistic behaviours in computer-mediated communication (CMC) contribute to identity construction and community cohesion. This study is framed by Gerry Philipsen’s Speech Codes Theory, which offers a framework for analyzing the cultural codes embedded in communication. It employs a netnography research design, using data sampled from distinct social media groups dedicated to blockchain discourse. Textual data from posts, comments, and interactions were subjected to content analysis to identify speech codes and their functions in constructing community identity. The findings reveal that blockchain communities utilize a distinct lexicon, marked by technical jargon, memes, and ideologically charged phrases. Additionally, language usage reflects underlying tensions between inclusivity and exclusivity, particularly in the negotiation of novice versus expert identities. The study concludes that language is central to identity construction in blockchain communities, functioning as both a tool for social bonding and a mechanism of gatekeeping. This research contributes to understanding the role of language in digital identity formation and offers insights into the cultural dynamics of emerging technological communities.